Analysis of the Hydrolytic Capacities of Aspergillus oryzae Proteases on Soybean Protein Using Artificial Neural Networks. Issue 5 (3rd December 2015) - Li, Shiwen; Hu, Yong; Hong, Yingmin; Xu, Libin; Zhou, Mengzhou; Fu, Caixia; Wang, Chao; Xu, Ning; Li, Dongsheng
Abstract: An artificial neural network (ANN) model was established to predict the hydrolytic capacities of A spergillus oryzae proteases on soybean protein. The available training data were split in two subsets: training and testing data, which comprised 25 and six groups of proteases, respectively. These data served as the inputs of ANN to predict small peptide content, degree of hydrolysis and free amino nitrogen content. This network included three neurons in the single hidden layer with a low mean squared error. The predicted results were similar to the actual values ( R 2 > 0.92) and were superior to those of multiple linear regression. Sensitivity analysis revealed that there is a correlation between protease and soy protein hydrolysates. It was also verified that protease and soy protein hydrolysates could serve as inputs and outputs in the ANN. Among the tested proteases, aminopeptidase showed the highest hydrolytic capacity for soybean protein with sensitivity analysis. Practical Applications: The artificial neural network model is a powerful technique to predict the hydrolytic capacities of A spergillus oryzae proteases for soybean protein. The results of this study could be used to test the amount of yielded hydrolysates of soybean protein under one combination protease, and also explained the mechanism underlying the protease‐catalyzed hydrolysis of soybean.